Apparent Life-Threatening Events (ALTE): Italian guidelines - Raffaele Piumelli; Riccardo Davanzo; Niccolò Nassi; Silvia Salvatore; Cinzia Arzilli; Marta Peruzzi; Massimo Agosti; Antonella Palmieri; Maria Giovanna Paglietti; Luana Nosetti; Raffaele Pomo; Francesco De Luca; et al. (BMC, 2017)
Abstract Five years after the first edition, we have revised and updated the guidelines, re-examining the queries and relative recommendations, expanding the issues addressed with the introduction of a new entity, recently proposed by the American Academy of Pediatrics: BRUE, an acronym for Brief Resolved Unexplained Events. In this manuscript we will use the term BRUE only to refer to mild, idiopathic cases rather than simply replace the acronym ALTE per se. In our guidelines the acronym ALTE is used for severe cases that are unexplainable after the first and second level examinations. Although the term ALTE can be used to describe the common symptoms at the onset, whenever the aetiology is ascertained, the final diagnosis may be better specified as seizures, gastroesophageal reflux, infection, arrhythmia, etc. Lastly, we have addressed the emerging problem of the so-called Sudden Unexpected Postnatal Collapse (SUPC), that might be considered as a severe ALTE occurring in the first week of life.